2008
DOI: 10.1121/1.2904825
|View full text |Cite
|
Sign up to set email alerts
|

Spatial release from energetic and informational masking in a divided speech identification task

Abstract: When listening selectively to one talker in a two-talker environment, performance generally improves with spatial separation of the sources. The current study explores the role of spatial separation in divided listening, when listeners reported both of two simultaneous messages processed to have little spectral overlap (limiting "energetic masking" between the messages). One message was presented at a fixed level, while the other message level varied from equal to 40 dB less than that of the fixed-level messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 30 publications
6
48
1
Order By: Relevance
“…A related study also using the CRM corpus investigated the effect of differences in stream level on the benefit of spatial separation in a divided attention task (Ihlefeld and Shinn-Cunningham, 2008). Using different band tonevocoded speech with one stream at a fixed intensity and the other varying across trials from À40 to 0 dB (relative to the fixed-intensity stream), they found a pattern of performance and errors suggesting that listeners were prioritizing attention to the quieter (varying-intensity but fixed call-sign) stream, and reporting keywords from the fixed-intensity (but varying call-sign) stream based on recall from temporary storage.…”
Section: Introductionmentioning
confidence: 99%
“…A related study also using the CRM corpus investigated the effect of differences in stream level on the benefit of spatial separation in a divided attention task (Ihlefeld and Shinn-Cunningham, 2008). Using different band tonevocoded speech with one stream at a fixed intensity and the other varying across trials from À40 to 0 dB (relative to the fixed-intensity stream), they found a pattern of performance and errors suggesting that listeners were prioritizing attention to the quieter (varying-intensity but fixed call-sign) stream, and reporting keywords from the fixed-intensity (but varying call-sign) stream based on recall from temporary storage.…”
Section: Introductionmentioning
confidence: 99%
“…In a sense, however, the issues raised by the decrement in performance due to concurrent presentation can be considered an instance of the general dual task with separate processing and decisions made for each stimulus (cf., Navon and Gopher, 1979;Bonnel and Hafter, 1998;Gallun et al, 2007). Performance in similar conditions requiring judgments of complex stimuli have been reported under conditions of high uncertainty with large costs often associated with the dual-task (e.g., Best et al, 2006;Ihlefeld and Shinn-Cunningham, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, while accomplishing this task, the listener also must remain vigilant with respect to the composition of the sound field so that important changes (e.g., new sources) are recognized and processed rapidly and appropriately. Although there have been studies examining the ability of listeners to perform two auditory tasks simultaneously under conditions of high uncertainty (e.g., Best et al, 2006;Gallun et al, 2007;Ihlefeld and Shinn-Cunningham, 2008;Helfer et al, 2010), comparatively little is known about how listeners perceive and evaluate two concurrent streams of sound.…”
Section: Experiments Three: Successive Versus Concurrent Comparisonmentioning
confidence: 99%
“…The volume level of the podcast was attenuated by approximately -10 dB by moving the source to the right hand-side (-3 dB intensity drop) and doubling the perceived distance by placing it 2m away from the listener. Listeners have been shown to perform best when monitoring an audio stream at -10 dB, compared to lower levels [7].…”
Section: Concurrentmentioning
confidence: 99%
“…By modelling the filter based on the transfer function between the sound source located at certain positions and the eardrums of a listener (the Head Related Transfer Function, HRTF), it is possible to position audio effectively all around a user. A spatial representation of the auditory display provides orientational information that aids segregation and attention switching between the audio streams to maintain intelligibility when auditory information is being used [6,7]. However, it is less clear how 3D audio techniques might be implemented in an interactive environment, where we need to consider how to manage multiple audio streams without overloading the user.…”
Section: Introductionmentioning
confidence: 99%